Synthesis and electrochemical study of iron, chromium and tungsten aminocarbenes: Role of ligand structure and central metal nature - Hoskovcová, Irena; Roháčová, Jana; Dvořák, Dalimil; Tobrman, Tomáš; Záliš, Stanislav; Zvěřinová, Radka; Ludvík, Jiří (Electrochimica acta, 2010)
Several series of Fischer-type aminocarbene complexes with central Fe, Cr or W atoms and with various carbene substitution were synthesized and electrochemically investigated by dc-polarography and cyclic voltammetry. The shifts and changes of reduction and oxidation potentials were evaluated using the linear free energy relationship (LFER) approach with respect to (a) the type of coordination, (b) the substitution on the carbene ligand and (c) the nature of the central metal atom. The analysis of measured data confirms that the reduction center is localized on the carbene moiety and is strongly influenced by both electronic and sterical properties of its substituents. The oxidation proceeds on the metal and depends mainly on its nature and on the π-acidity of the ligands. Electrochemistry thus represents an important experimental approach to the description and understanding of the molecular electronic structure and redox properties. Experimental results are supported by DFT calculation of HOMO and LUMO orbitals shape and composition.